Factors Affecting Compliance to Ethical Standards in Public Procurement in Kenya: A Behavioral Model of Ethical and Unethical Decision Making Perspective - Bosire Okemwa, Victor; Matayo Ratemo, Dr. Bonface (International Journal of Scientific Research and Management (IJSRM), 2021)
The study sought to investigate the factors affecting compliance to ethical standards in public procurement in Kenya. The study adopted it is specific objectives from a behavioral  model of ethical and unethical decision making that is; professionalism factors, social factors, personality factors, legal framework factors and work environment factors on how they affect compliance to ethical  standards in public procurement in Kenya. The study adopted descriptive research design as the study design, the population of the study was 40 employees and since the population was small the researcher employed census research design where all employees took part in the research. Primary data collection method was used by administering structured questionnaires. Descriptive statistics, correlation and multiple regression analysis were used to analyze the data. The finding of the study revealed that professionalism factors, legal framework factors, and work environment factors had a positive and statistical significant influence on compliance to ethical standards in public procurement in Kenya. Personal factors and social factors were found not to have statistical significant influence on compliance to ethical standards in public procurement in Kenya. The study recommended that administrative bodies and judiciary should enforce sanction to people who contravenes rules and code of ethics in public procurement. Public organization to invest in training their employees in public procurement code of ethics and rules to avoid the ignorance’s currently observed. This study had implications on knowledge and practices since it did not only investigate factors affecting compliance to ethical standards in public procurement in Kenya but also informed that professionalism factors, legal framework factors and work environment factors were the major factors affecting compliance to ethical standards in public procurement in Kenya.